Chemical profile and antioxidant potential of extractable and non‐extractable polyphenols in commercial teas at different fermentation degrees. Issue 6 (27th April 2020) - Yan, Shuaishuai; Zhou, Zhihao; Wang, Kaijie; Song, Shixi; Shao, Hongjun; Yang, Xingbin
Abstract: The present study aimed to compare the chemical and antioxidant differences between the extractable and non‐extractable polyphenols (EPP and NEPP) in commercial teas with different fermentation degrees. The results showed that both content and antioxidant activity of NEPP were lower than EPP regardless of fermentation degrees of teas. One white tea, Baekho Silver Needle (BSN), had the highest NEPP content (58.38 ± 0.73 mg GAE/g DW) by alkaline hydrolysis, as well as the antioxidant activities among different teas studied. Meanwhile, alkaline hydrolysis also was the most effective method in extracting the NEPP from these teas, followed by acid and enzymatic hydrolysis. Combined principle component analysis and hierarchical clustering analysis demonstrated that gallic acid (GA), epigallocatechin (EGC), and gallocatechin (GC) were three major components in the NEEP studied, with the highest content 13.89 ± 0.87 mg/g DW in BSN, 16.14 ± 1.24 mg/g DW in Dianhong (DH), and 7.26 ± 0.55 mg/g DW in Biluochun (BLC), respectively. GA also was found to be the main contributor to antioxidant activity of NEPP. In addition, NEPP with different fermentation degrees showed discriminations in total polyphenols content, phytochemical profiles, and antioxidant activities but were disorder with the fermentation degrees of these teas. These results provided more information for NEPP in teas with different fermentation degrees including the phytochemical profiles and optimal extraction method. Practical applications: NEPP have long been underestimated or neglected because this part of polyphenolic fraction cannot be extracted from the residues by aqueous or organic solvents. This study systematically investigated phytochemical profiles and antioxidant activity of EPP and NEPP in commercial teas with different fermentation degrees. Comparing the release efficacy of tea NEPP by different extraction methods indicated that tea residues were still a considerable source for NEPP. Profiles of polyphenols in teas with different fermentation degrees can be better uncovered according to this study to improve the health.